Managing Common Interventional Radiology Complications A Case Based Approach - Ratnam, Lakshmi; Patel, Uday.; Belli, Anna Maria; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Managing Common Interventional Radiology Complications: A Case Based Approach is an easy-to-use manual that will help trainees and practising radiologists by providing cases which cover most of the complications that a general interventionalist may encounter in normal practice. The cases are presented succinctly but thoroughly, so that the reader is equipped to manage the complication immediately. Managing Common Interventional Radiology Complications: A Case Based Approach aims to teach the range of procedures involved in interventional radiology, and focuses on the complications that can arise in the process.
1. Embolisation coil trapped in the side hole of a catheter -- 2. Retrieval of an intravascular foreign body in the venous system -- 3. Migrated Superior Vena Cava Stent Repositioned using a Balloon and Loop Snare Combination -- 4. Retrieval of Central Venous Catheter fragment following Portacath Removal -- 5. Central Venous Catheter Inserted Into the Mediastinum -- 6. Femoral artery pseudoaneurysm treated with percutaneous thrombin injection -- 7. Superficial Femoral Artery Thrombosis Post Angioplasty -- 8. Superficial Femoral Artery Rupture Following Angioplasty -- 9. Distal embolization following common iliac and superficial femoral artery angioplasty -- 10. Flow-limiting iliac artery dissection post angioplasty -- 11. Dissection of Superior Mesenteric Artery (SMA) during Transarterial Chemoembolisation (TACE) via a replaced right hepatic artery -- 12. Iatrogenic iliac artery rupture during arterial stenting -- 13. Detachment of a balloon-expandable stent from the balloon and the wire -- 14. Migration of common hepatic artery stent graft occluding right hepatic artery flow -- 15. Migrated stent graft during TIPS revision -- 16. Type 1A Endoleak following EVAR treated with a Proximal Cuff -- 17. Management of a Type 1B Endoleak following EVAR.-18. Persistent Type 2 Endoleak Post EVAR With Aneurysm Expansion -- 19. Acute Renal Artery Occlusion and Trapped Renal Artery Catheter during Infrarenal AAA Stent-grafting -- 20. Maldeployment of the contralateral limb during EVAR -- 21. Branch endograft disconnection and impending type 3 endoleak post EVAR -- 22. Haemorrhage following percutaneous nephrostomy -- 23. Injury to bowel following transplant nephrostomy insertion -- 24. Renal arterial haemorrhage following renal artery stenting -- 25. Pyrexia after Tumour Embolisation - Infection vs Post-embolisation Syndrome -- 26. Arterioportal fistula and Liver haemorrhage after Radiofrequency Ablation and TACE -- 27. Protrusion of vena cava filter into the aorta -- 28. Multiple Options for Retrieval of a Tilted IVC filter -- 29. Retrieval of a Well Orientated IVC Filter with Embedded Struts -- 30. Retrieving a Tilted IVC filter with Struts Penetrating the IVC -- 31. Fistula rupture post fistuloplasty -- 32. Circumferential balloon rupture and retained fragments during fistuloplasty; and thrombolysis of a thrombosed fistula -- 33. Haemorrhage after Transjugular Liver Biopsy.
Keywords: Medicine; Radiology, Medical; Interventional radiology; Medicine & Public Health; Interventional Radiology; Imaging / Radiology